2013
DOI: 10.1111/bju.12067
|View full text |Cite
|
Sign up to set email alerts
|

Validation of serum C‐reactive protein (CRP) as an independent prognostic factor for disease‐free survival in patients with localised renal cell carcinoma (RCC)

Abstract: Objective• To validate high-sensitivity C-reactive protein (hs-CRP) serum levels as an independent marker for disease-free survival (DFS) in clinically localised clear cell renal cell carcinoma (ccRCC). Patients and Methods• In all, 403 consecutive patients with clinically localised (T1-3N0M0) ccRCC treated by radical or partial nephrectomy were enrolled.• Preoperative serum levels of hs-CRP were evaluated as both a continuous and categorical variables.• Associations with clinical (age, gender) and pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Numerous serum inflammation markers, such as CRP [6][7][8][9][10], have proven to be good prognostic indicators in patients with a variety of malignancies, but they require separate laboratory testing. The easily calculated NLR, on the other hand, has shown utility as an alternative marker of systemic inflammation in critically ill patients [19], malignancies [20], and chronic medical conditions such as end-stage renal disease and diabetes [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous serum inflammation markers, such as CRP [6][7][8][9][10], have proven to be good prognostic indicators in patients with a variety of malignancies, but they require separate laboratory testing. The easily calculated NLR, on the other hand, has shown utility as an alternative marker of systemic inflammation in critically ill patients [19], malignancies [20], and chronic medical conditions such as end-stage renal disease and diabetes [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…There is now an ample body of literature on the association between chronic inflammation and cancer [1][2][3][4], with an estimated 15% of malignancies worldwide being reported as having an infectious association or etiology [5]. C-reactive protein (CRP), a serum marker for systemic inflammation, has shown good prognostication in patients with renal cell carcinoma (RCC) [6][7][8][9][10] and similar findings when combined with serum albumin levels in the modified Glasgow Prognostic Score [3]. However, CRP requires additional serum testing and hence is not readily available for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic significance of serum CRP was found in various cancer patients and in the advanced stage of cancers, including renal cell carcinoma [34], [35], [36], [37], [38], [39], [40], bladder [41], [42], [43], [44], breast [45], [46], [47], [48], [49], [50], stomach [51], , colon and rectum [56], , head and neck [62], [63], [64], esophagus [25], [65], [66], [67], [68], [69], prostate [70], [71], [72], [73], [74], lung [75], [76], [77], [78], [79] and pancreatic cancer [80], [81]. The high CRP levels have also been associated with aggressive diseases and poor survival outcomes for these malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 43 eligible studies (7, 490 patients) were identified for this meta-analysis (25 for RCC (Atzpodien et al, 2003;Bromwich et al, 2004;Casamassima et al, 2005;Peccatori et al, 2005;Ito et al, 2006;Lamb et al, 2006;Vogl et al, 2006;Karakiewicz et al, 2007;Komai et al, 2007;Ramsey et al, 2007;Kawata et al, 2008;Ramsey et al, 2008;Tanaka et al, 2008;Iimura et al, 2009;Jagdev et al, 2010;Cho et al, 2011;Falkensammer et al, 2011;Bedke et al, 2012;Fujita et al, 2012;Sim et al, 2012;Steffens et al, 2012;de Martino et al, 2013;Yasuda et al, 2013), 10 for UC (Hilmy et al, 2005;Hilmy et al, 2006;Saito et al, 2007;Yoshida et al, 2008;Gakis et al, 2011;Saito and Kihara, 2011;Ishioka et al, 2012;Obata et al, 2012;Tanaka et al, 2012;Stein et al, 2013), and 8 for PC (McArdle et al, 2006;Beer et al, 2008;Nakashima et al, 2008;McArdle et al, 2010;Pond et al, 2012;Prins et al, ...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%